Checkpoint inhibitor–induced lichen planus differs from spontaneous lichen planus on the clinical, histological, and gene expression level - Meier-Schiesser, Barbara; Zecha, Christine; Zierold, Sarah; Kolm, Isabel; Röckel, Magdalena; Fröhlich, Waltraud; Mittag, Nora; Schmitt, Christina; Kumbrink, Joerg; Hassel, Jessica C.; Berking, Carola; Nashan, Dorothee; et al. (Journal of the American Academy of Dermatology, 2024)
Background: Although highly efficacious, immune checkpoint inhibitors induce a multitude of immune-related adverse events including lichenoid skin reactions (irLP) that are often therapy-resistant. Objectives: To compare the clinical, histological, and transcriptional features of irLP with spontaneous lichen planus (LP). Methods: Clinical and histological presentations of irLP and LP, as well as the gene expression profiles of irLP and LP lesional and healthy skin were assessed. Results: irLP differed considerably from LP with regard to the distribution pattern of skin lesions with irLP appearing mostly in an exanthematous form, whereas lesions were more localized in the LP group. Histologically, dermal lymphocyte infiltration was significantly lower in irLP compared with LP, whereas lymphocyte exocytosis and apoptotic keratinocytes were significantly higher in irLP. Gene expression analysis revealed irLP to have a more inflammatory profile with elevated IFNG levels and a possible role of phagosome signaling compared with LP. Limitations: The study is descriptive and necessitates further investigation with larger cohorts and broader analyses. Conclusion: irLP differs from spontaneous LP on the clinical, histopathological, and gene expression level. The inflammatory gene signature in irLP suggests that topical JAK inhibitors could be an effective treatment, targeting local skin inflammation without systemic immunosuppression.
CRIS-Team Scopus Importer:2024-04-05
Keywords: cutaneous side effects; exanthematous; gene expression profiles; immune-related adverse events; inflammatory signatures